Silencing of IRF8 Mediated by m6A Modification Promotes the Progression of T‐Cell Acute Lymphoblastic Leukemia. Issue 2 (7th December 2022) - Zhou, Ying; Ji, Min; Xia, Yuan; Han, Xiaoyu; Li, Mingying; Li, Wei; Sun, Tao; Zhang, Jingru; Lu, Fei; Sun, Yanping; Liu, Na; Li, Jingxin; et al.
Abstract: T‐cell acute lymphoblastic leukemia (T‐ALL) is an aggressive hematological malignancy with a poor prognosis, urging for novel therapeutic targets and treatment strategies. N6 ‐methyladenosine (m6A) is a crucial methylation modification that affects the pathogenesis of leukemia by regulating the mRNA of key genes. Interferon regulatory factor 8 (IRF8) is a crucial transcription factor for hematological lineage commitment, but its role in T‐ALL is unclear. Here, IRF8 is shown to suppress T‐ALL. The expression of IRF8 is abnormally silenced in patients with T‐ALL. Knockout of Irf8 significantly hastens the progression of Notch1‐induced T‐ALL in vivo. Overexpression of IRF8 suppresses the proliferation and invasion of T‐ALL cells by inhibiting the phosphatidylinositol 3‐kinase/AKT signaling pathway. The fat mass‐ and obesity‐associated protein (FTO), an m6A demethylase, is responsible for directly binding to m6A sites in 3′ untranslated region of IRF8 messenger RNA (mRNA) and inducing mRNA degradation via m6A modification. Targeting the FTO‐IRF8 axis is used as a proof of concept therapy; inhibition of FTO's demethylase activity drastically alleviates the proliferation of leukemic cells and prolongs the survival of T‐ALL mice by restoring IRF8 expression. This study elucidates the pathogenesis of T‐ALL from the perspective of epitranscriptomics and provides new insight into the genetic mechanisms and targeted therapy of T‐ALL. Abstract : Suppressed interferon regulatory factor 8 (IRF8) contributes to cell proliferation and leukemogenesis of T‐cell acute lymphoblastic leukemia (T‐ALL) via transcriptional regulation of PIK3R5 and activation of phosphatidylinositol 3‐kinase (PI3K)/AKT pathway. High expression of fat mass‐ and obesity‐associated protein (FTO) in T‐ALL inhibits IRF8 expression by binding to m6A sites in 3' untranslated region (UTR) of IRF8 messenger RNA (mRNA) and erasing m6A methylation modification, thereby promoting IRF8 mRNA degradation.